Research on Promoting the Sustainable Development of Green Building through BIM Application-From the perspective of the whole building lifecycle - et. al., Hong Cheng Ma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Building Information Modeling (BIM) is a digitalized technology on the basis of a collaborative working platform that can offer effective solutions in the entire building lifecycle. Abundant building information can be integrated through the application of BIM technology to solve the problems that are otherwise difficult to deal with at various stages of construction projects including preliminary planning, schematic design, construction management, as well as operation and maintenance. New means can also be provided through the innovation driven by BIM to reduce the impact of construction projects on environment during the process of construction and development in the building lifecycle. Based on relevant application research, this paper focuses on the sustainable development in the entire building lifecycle of green building, puts forward some suggestions, and points out the problems that should be paid attention to in BIM application. At the same time, the paper proposes some application plans based on BIM technology to promote data sharing in the lifecycle of green building projects, to achieve sustainable development of green building at different stages including project planning, design, construction, as well as operation and maintenance management, and to develop the BIM application system for the sustainable development in the entire building lifecycle of green building.